PERBANDINGAN SISTEM HUBUNGAN KERJA PKWTT DAN PKWT DALAM UPAYA PENINGKATAN KESEJAHTERAAN PEKERJA - Rudi Avianto; Endeh Suhartini; Achmad Jaka Santos Adiwijaya (JURNAL ILMIAH LIVING LAW, 2022)
The Employment Relations System occurs by a work agreement between Workers and Employers. This employment relationship is regulated in Law No. 13 of 2003 concerning Manpower in Chapter IX Articles 50-66, which known as Employment contract for an unlimited time (PKWTT) and the Employment Contract Limited Time (PKWT). The aim of this research are : 1) to know the policies of the PKWTT and PKWT employment relations systems for the companies. 2) to know the comparison of the PKWTT and PKWT employment relations systems for the companies which associated with the efforts to improve workers welfare. The research method used is sociological juridical research. From the research results, it is known that the PKWTT and PKWT employment relations system policies, the percentage of PKWTT workers is greater, which is around 60% (PKWTT) and 40% (PKWT), including the comparison of rights and welfare facilities is better for PKWTT workers. For this reason, government regulations regarding rights and welfare facilities are needed for PKWT workers, so that they can be aligned or balanced.